KARAKTER TOKOH UTAMA DALAM NOVEL LAA ANAAM KARYA IHSAN ABDUL QUDDUS (SUATU TINJAUAN INTRINSIK) - , Linda; Haeriyyah; Ilham Ramadhan (Jurnal Sarjana Ilmu Budaya, 2024)
This thesis is an analysis of the main characters in the novel entitled "Laa Anam" by Ihsan Abdul Quddus. This novel tells the story of a girl who experiences an Electra complex, which is excessive interest in her father so she feels that she is competing with her stepmother in getting her father's attention, besides that she has a unique character because of her complex nature. This research is qualitative with a literature review method. The method used in collecting data is reading and note-taking techniques. Meanwhile, the analytical technique used is content analysis. The review used in this study is an intrinsic review, namely a review that examines the intrinsic elements in a literary work and the focus of this research is the main character in the novel "Laa Anaam" by Ihsan Abdul Quddus. After doing research, it was found that Nadia has a character, namely Self-confident, clever, manipulative, evil, a complex personality, sympathy, liar, responsible, arrogant, introvert, quiet, smart, bigoted to his father, hypocrite, jealous, angry person, have envious nature, vengeful, strong determination, conscientious, easily anxious/overthinking, spoiled, shy, stubborn, brave, selfish, and loyal. Meanwhile, in determining the depiction of characters, it is divided into two, namely analytical techniques and dramatic techniques. Depictions with analytic techniques or depictions of characters by giving direct descriptions, then Nadia's character includes the following five characters: evil, responsible, quiet, envious, and brave. Meanwhile, the depiction of characters with dramatic techniques or indirect depictions of characters, then Nadia's character includes 18 characters, namely: self-confident, smart, manipulative, loving woman, introvert, fanatical to her father, hypocritical, easily jealous, short-tempered, vengeful, determined, careful, easily anxious/overthinking, spoiled, shy, selfish, and loyal. In addition, there are four characters who are depicted using analytical and dramatic techniques, namely complex, arrogant, clever, and stubborn personalities. Keywords: Main Character, Novel, Character